Islamic Principles in Efforts to Prevent Accounting Fraud - Amin, Asbi; Hamid Habbe, Abdul; Wahab, Abdul (Dinasti Publisher, 2021)
Weak internal control is generally caused by the internal environment and the external environment. Among several types of fraud. Financial statement fraud is the type of fraud that has the most detrimental effect of fraud. Islam has set values, concepts in regulating ethics and regulations so that this life runs according to rules and harmony. Economic activities in Islam are not only oriented to worldly and contemporary interests, but also to ukhrawi benefits. Spirituality is the greatest meaning and purpose in a person's life which is considered capable of providing a more positive reciprocal relationship between the organization and its members, and enabling everyone to work together and achieve the same goals. Therefore, to avoid fraud, Islam threatens a lot and warns in its argument that there will be retaliation for cheating. Religiosity with the principles of faith, morals and trust is the main capital for preventing fraud.